Lifestyle of university students from a confessional institution in northwest Paraná (Research, Society and Development, 2023)
Objective: to evaluate the lifestyle of university students at a confessional institution in northwestern Paraná. Methodology: Cross-sectional, descriptive study, with a quantitative approach. Data were collected using a validated questionnaire (Fantastic Lifestyle), applied to 297 higher education students from a private educational institution in the northwest of Paraná, and analyzed using Software R. The research was approved by the Research Committee. Research Ethics (Opinion no. 3,578,524), and met the regulatory standards for research involving human beings. Results: Of the students analyzed, 37.7% were classified as having an “excellent” lifestyle, 46.1% as “very good”, 14.1% were classified as “good”, 2% “average” and none were classified as “needs improvement”. The variables that had a statistically significant association with lifestyle were: having someone to talk to, giving and receiving affection, being positive and optimistic, being able to deal with stress, being satisfied with work, relaxing and having leisure time, practice physical activity (vigorously or moderately active) and sleep well. The variables that had a negative association with lifestyle were: frequently eating junk food, being above a healthy weight range, feeling sad and depressed, appearing to be in a hurry. Conclusion: The vast majority of students analyzed presented a lifestyle considered excellent and very good, a superior result when compared to other studies, which may be associated with the fact that they study and live in an environment that encourages a healthy lifestyle.